(3cJGH cTa GdJfHjgGJs - (3eMeO Hf YHO GdhgGH Hf SdjeGf GdJejej GdfLOj , J (B1206 (3g`s
(3ChdgG (B:s
(3EYde habc Gddg Cf GdJhMjO gh EaQGO Gddg SHMGfg HGdhMOg s
(3BNQgG (B:s
(3aGKQg Ydi GdOjf hGddg SHMGfg hJYGdi CYde hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3eUOQ GbJfGA GdCUd (B:s
(3GdEeHQhRjGfG (B(404 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds